Developing Learning Professionals
XX, 220 p.
Keywords: In higher education institutions across the globe, there is a growing interest in integrating classroom learning with experience in practice settings. This interest is the result of an increased emphasis on courses that prepare students for specific occupations in the hopes that upon graduation students will be job-ready. Developing Learning Professionals: Integrating Experiences in University and Practice Settings explores how the integration of student experiences across university and practice settings might best be used to produce college graduates who are adept, critical practitioners. To do so, it draws on the findings of a series of projects in Australia that investigated diverse aspects of work-related learning. Through these projects, a range of scholars and researchers consider different aspects of this educational initiative within the same national higher education context. They address pedagogic and curriculum practices, institutional arrangements andpartnerships of varying kinds, and a consolidated set of perspectives.